Light-absorbing impurities accelerating glacial melting in southeastern Tibetan Plateau. (February 2020) - Niu, Hewen; Kang, Shichang; Wang, Hailong; Du, Jiankuo; Pu, Tao; Zhang, Guotao; Lu, Xixi; Yan, Xingguo; Wang, Shijin; Shi, Xiaofei
Abstract: Deposition of light-absorbing particles on glacier surfaces poses a series of adverse impacts on the cryospheric environment, climate and human health. Broad attention of the scientific community has been paid on insoluble light-absorbing impurities (ILAIs) in snow and ice on glaciers over the Tibetan Plateau (TP). However, systematic investigation of ILAIs in snowpack of glaciers on the TP is scarce. In this study, the properties and darkening effect of ILAIs in snowpack on glaciers are extensively investigated in the southeast of TP. Results show that ILAIs concentrations in multiple types of snow and ice samples were significantly different. Snowpit depths varied substantially from one profile to another during May and June 2016. The average concentrations of ILAIs in snowpits increase as snow melting progresses. Black carbon (BC) and dust cause snow albedo reduction more in snow with larger grain size R e . Based on a radiative transfer model calculation, the average albedo reduction induced by BC in the snowpack was 0.141 ± 0.02, and associated daily maximum radiative forcing ( RF ) was 72.97 ± 12.7 W m −2 . BC is a controlling light-absorbing factor in snowpack and causes substantial albedo reduction and thus the associated daily maximum RF . The maximum reduction of snow cover duration was 4.56 ± 0.71 days caused by BC and dust in snowpack in southeastern TP. The average mass absorption cross-section (MAC) of BC from multiple snowpits was 3.26 ± 0.46 m 2 g −1, which represents a typical value of MAC in snow on glaciers, but it is type-dependent of snow/ice samples. Tropospheric aerosols vertically extended up to 8 km over the TP and its surrounding areas, which indicates the transport of aerosols from remote sources through elevated pathways. A large amount of carbon stored in the brittle glaciers can be potentially released with meltwater runoff under a warming climate. This study provides a new insight for investigating carbonaceous and light-absorbing particles in glacierization areas. Graphical abstract: Image 1 Highlights: BC and dust cause significant reductions of snow cover duration and snow albedo. Runoff discharge in the southeastern Tibetan Plateau (TP) arrived a month earlier in 2014 than in 2009. The average mass absorption cross-section (MAC) of BC from multiple snowpits was 3.26 ± 0.46 m 2 g −1 The BC MAC value is found to be type-dependent of snow/ice samples.